[Ag(I)(Et2PCH2CH2PPh2)2]NO3: An Antimitochondrial Silver Complex. Issue 2 (1995) - Berners-Price Berners-Price, Susan J. Susan J.; Collier Collier, Doreen C. Doreen C.; Mazid Mazid, Muhammed A. Muhammed A.; Sadler Sadler, Peter J. Peter J.; Sue Sue, Rodney E. Rodney E.; Wilkie Wilkie, David David
Abstract : The silver(I) complex [Ag(eppe) 2 ]NO 3 (eppe = Et 2 PCH 2 CH 2 PPh 2 ) is shown by X-ray crystallography to be tetrahedral with Ag - PEt 2 and Ag - P Ph 2 bond lengths of 2.482 and 2.518 Å, respectively. The complex is selectively antimitochondrial and inhibits the growth of a number of yeast strains in non-fermentable media at concentrations as low as 2.5 μΜ and induces the mitochondrial mutation petite The effect is largely reversed by the presence of aspirin. The complex is shown to be stable in the cell culture media and in the presence of glutathione, but readily reacts with disulfides of oxidized glutathione and serum albumin. Surprisingly, neither [ Au ( eppe ) 2 ] Cl nor [ Au ( dppe ) 2 ] Cl (dppe = Ph 2 PCH 2 CH 2 PPh 2 ) showed any mitochondrial selectivity in the same screening protocol.